PENGGUSURAN SEBAGAI IMPLIKASI KEBIJAKAN RUANG TERBUKA HIJAU DALAM PERSPEKTIF HAM: STUDI KASUS PENGGUSURAN TAMAN BERSIH, MANUSIAWI DAN BERWIBAWA (BMW) - Siti Manggar Fathani (Jurnal Kriminologi Indonesia, 2011)
This research lifts up issues on forced eviction as an impact of green space policy, with the case study of forced eviction in BMW’s Park. The research views forced eviction in Taman BMW through human rights aspect, where the notions of human rights is to make sure that every citizen secures guarantee of human rights from the state. To find data of this research the researcher did the field research by interacted with the subject and interviewed the expert from National Commission of Human Rights and Jakarta’s Law Aid Foundation. This research uses descriptive qualitative approach, where the data were collected by using literature study, interview, observation and interaction to whom are appropriate to this research. In conclusion, this research found that forced eviction happened in BMW’s Park gives a lot of victim of human rights violation and the state is charge, of the human rights violation.